Comparative analysis of CRISPR‐Cas systems in Klebsiella genomes. (3rd February 2017) - Shen, Juntao; Lv, Li; Wang, Xudong; Xiu, Zhilong; Chen, Guoqiang
Abstract : Prokaryotic CRISPR‐Cas system provides adaptive immunity against invasive genetic elements. Bacteria of the genus Klebsiella are important nosocomial opportunistic pathogens. However, information of CRISPR‐Cas system in Klebsiella remains largely unknown. Here, we analyzed the CRISPR‐Cas systems of 68 complete genomes of Klebsiella representing four species. All the elements for CRISPR‐Cas system (cas genes, repeats, leader sequences, and PAMs) were characterized. Besides the typical Type I‐E and I‐F CRISPR‐Cas systems, a new Subtype I system located in the ABC transport system‐glyoxalase region was found. The conservation of the new subtype CRISPR system between different species showed new evidence for CRISPR horizontal transfer. CRISPR polymorphism was strongly correlated both with species and multilocus sequence types. Some results indicated the function of adaptive immunity: most spacers (112 of 124) matched to prophages and plasmids and no matching housekeeping genes; new spacer acquisition was observed within the same sequence type (ST) and same clonal complex; the identical spacers were observed only in the ancient position (far from the leader) between different STs and clonal complexes. Interestingly, a high ratio of self‐targeting spacers (7.5%, 31 of 416) was found in CRISPR‐bearing Klebsiella pneumoniae (61%, 11 of 18). In some strains, there even were multiple full matching self‐targeting spacers. Some self‐targeting spacers were conserved even between different STs. These results indicated that some unknown mechanisms existed to compromise the function of self‐targets of CRISPR‐Cas systems in K. pneumoniae .